A "crackleware" oesophagus. Issue 12 (25th November 2005) - Westerterp, M; Busch, O R C; Bergman, J J G H M; ten Kate, F J W; van Lanschot, J J B
Abstract : This case report describes a 70 year old woman with excessive diffuse keratinisation of the oral cavity and oesophagus harbouring a squamous cell carcinoma. This excessive diffuse keratinisation of normally non-keratinised squamous epithelium could not be identified in normally non-keratinised epithelia in other parts of the body (the vagina), arguing against a genetic basis for this disorder. The term "crackleware" oesophagus was used to describe this entity, which has not been described previously in the English literature.